Guide to Discrete Mathematics - O’Regan, Gerard (Springer, 2016)
The objective of this book is to give the reader a flavor of discrete mathematics and its applications to the computing field. The goal is provide a broad and accessible guide to the fundamentals of discrete mathematics, and to show how it may be applied to various areas in computing such as cryptography, coding theory, formal methods, language theory, computability, artificial intelligence, theory of databases, and software reliability. The emphasis is on both theory and applications, rather than on the study of mathematics for its own sake. There are many existing books on discrete mathematics, and while many of these provide more in-depth coverage on selected topics, this book is different in that it aims to provide a broad and accessible guide to the reader, and to show the rich applications of discrete mathematics in a wide number of areas in the computing field. Each chapter of this book could potentially be a book in its own right, and so there are limits to the depth of coverage for each chapter. However, the author hopes that this book will motivate and stimulate the reader, and encourage further study of the more advanced texts.
An Accessible Introduction to the History, Theory, Logic and Applications